Humane and Comprehensive Management of Challenging Behaviour in Health and Social Care: Cross-Sectional Study Testing Newly Developed Instrument - Tölli Sirpa; Kontio Raija; Partanen Pirjo; Terkamo-Moisio Anja; Häggman-Laitila Arja (MDPI, 2025)
Background:
Management of challenging behaviour causes victimization and violates the human rights of service users in psychiatric and long-term settings for people having mental health issues and learning disabilities. The purpose of the research was to develop and test an instrument for measuring humane behaviour management (HCMCB). The research was guided by the following questions: (1) What is the structure and content of the Human and Comprehensive management of Challenging Behaviour (HCMCB) instrument, (2) What are the psychometric properties of the HCMCB instrument, and (3) How do Finnish health and social care professionals evaluate their humane and comprehensive management of challenging behaviour?
Methods:
A cross-sectional study design and STROBE checklist were applied. A convenience sample of health and social care professionals (n = 233) studying at the University of Applied Sciences (n = 13) was recruited.
Results:
The EFA revealed a 14-factor structure and included a total of 63 items. The Cronbach's alpha values for factors varied from 0.535 to 0.939. The participants rated their individual competence higher than leadership and organizational culture.
Conclusions:
HCMCB is a useful tool for evaluating competencies, leadership, and organizational practices in the context of challenging behaviour. HCMCB should be further tested in various international contexts involving challenging behaviour with large samples and longitudinal design.